2018
DOI: 10.1021/jacs.7b12050
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Methane Hydrate in the Presence of Natural and Synthetic Nanoparticles

Abstract: Natural gas hydrates occur widely on the ocean-bed and in permafrost regions, and have potential as an untapped energy resource. Their formation and growth, however, poses major problems for the energy sector due to their tendency to block oil and gas pipelines, whereas their melting is viewed as a potential contributor to climate change. Although recent advances have been made in understanding bulk methane hydrate formation, the effect of impurity particles, which are always present under conditions relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 59 publications
6
51
0
Order By: Relevance
“…Concerning the nucleation of hydrates, an important question that is being addressed by the community concerns the effect on the nucleation rate due to the proximity of mineral surfaces and the presence of impurities. Recently, Cox et al 133 combined atomistic MD simulations with neutron scattering experiments to address this question and reported no effect on hydrate nucleation due to the presence of a wide variety of nanoparticles. These results seem to be consistent with coarse-grained simulations by DeFever and Sarupria, 134 who showed that even in proximity of an interface nucleation follows a bulk-like mechanism.…”
Section: Some Advancements In the Understanding Of Clathrate Hydratesmentioning
confidence: 99%
“…Concerning the nucleation of hydrates, an important question that is being addressed by the community concerns the effect on the nucleation rate due to the proximity of mineral surfaces and the presence of impurities. Recently, Cox et al 133 combined atomistic MD simulations with neutron scattering experiments to address this question and reported no effect on hydrate nucleation due to the presence of a wide variety of nanoparticles. These results seem to be consistent with coarse-grained simulations by DeFever and Sarupria, 134 who showed that even in proximity of an interface nucleation follows a bulk-like mechanism.…”
Section: Some Advancements In the Understanding Of Clathrate Hydratesmentioning
confidence: 99%
“…However, important questions about what kind of gaps and how they can be formed are still not clarified, because there is no valid scientific method to distinguish this type of gaps and semiclathrate in the pore, and quantitative analysis of the gas in gas hydrates or adsorptive phase is hardly carried out. Some techniques such as molecular simulations [11, 20], in situ Raman spectroscopy [21], solid-state nuclear magnetic resonance [10, 22], neutron diffraction [23, 24], and synchrotron X-ray powder diffraction [25] could only be employed to confirm that the formation of gas hydrates is dependent on porous materials. There is no doubt that gas hydrates could be formed on porous materials, but the details about the formation process and whether they are formed inside the pores or not are still ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…But, more than 70% of marine cementing faces the challenge of hydrate decomposition . Natural gas hydrates are a meta‐stable cage compound formed under low temperature and high pressure conditions, mainly distributed on the continental slope outside the continental shelf, sedimentary rock layers at the bottom of deep sea and deep lake and polar permafrost regions . Natural gas hydrates are essentially a potential new energy source, and the reserves are very large .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Natural gas hydrates are a metastable cage compound formed under low temperature and high pressure conditions, mainly distributed on the continental slope outside the continental shelf, sedimentary rock layers at the bottom of deep sea and deep lake and polar permafrost regions. [5][6][7] Natural gas hydrates are essentially a potential new energy source, and the reserves are very large. [8][9][10] However, in the development process of marine resources, hydrates put forward higher requirements for cement slurry.…”
Section: Introductionmentioning
confidence: 99%